IRON ORE MINING INDUSTRY OF UKRAINE IN A GLOBAL CONTEXT - MYKHAILOV, Volodymyr (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The structure of the iron ore mining industry of Ukraine, its role and significance in the world production of iron ores is considered. It is shown that the mining plants are one of the main budget-forming enterprises of Ukraine. An assessment of the state and forecasting of the development of the mineral and raw material base of iron ores of Ukraine was carried out, taking into account the state of the world market and a forecast assessment of its needs. The global trends in the development of the iron ore mining industry were considered, and it was shown that the general global trend over the last pre-war 5 years (2017–2021) was a gradual increase in iron ore production. A brief description of the iron ore basins of Ukraine is given. The most important mining enterprises of Ukraine are characterized. It is shown that iron ore is a traditional type of mining raw material of Ukraine, the investment attractiveness of which is based on significant reserves, many years of development experience, and developed infrastructure.
Keywords: mineral and raw material base; deposit; iron ore; mining and beneficiation plant; investments